Discovering the experiences of contralateral movement across the midline by teachers and their students - Spalding, Joan, author; Tompson, William M., advisor; Lehmann, Jean P., advisor; Foster, Ann, committee member; Hickey, Matthew, committee member (Colorado State University. Libraries, 2005)
This study explored teachers' perceptions about the use of Brain Gym® midline movement exercises to improve students' posture, focus, and behavior in the classroom. Brain Gym®, the registered trademark for Educational Kinesiology, is a learning readiness process to educate the mind/body system through midline movement activities. Two pilot studies guided the design of this case study research. Sixteen teachers and 63 students from 11 different public or private schools participated by using 26 midline-crossing exercises for a period of eight weeks. Thirty-nine students were males, 24 students were females. Students' ages ranged from 6 to 11 years old; the mean being nine years. All students were identified as having some sort of learning or physical challenge including ADD or ADHD. Data was obtained from teachers who reported about their own changes and those of their students using the Brain Gym® exercises daily. Data were collected on student observation forms and analyzed using visual analog scales. Findings showed that teachers perceived 33% of the students made improvements in their posture, focus, and behavior. Most students (54%) showed varied improvements and the remaining 13% were perceived as not demonstrating any improvements. Teachers also perceived that for children with physical challenges; 48% improved minimally, 39% demonstrated some improvement, and 13% greatly improved. According to teachers, students who did not learn to cross the midline were also unable to focus on their work and or to decrease their behavioral outbursts. Conversely, students who learned to cross the midline were noted to have higher reading, math, and handwriting scores. Other observations were that as students' posture became more stable, their sense of personal space was more defined. Furthermore, teachers perceived a greater calmness in the classroom and in their own demeanor as a result of implementing the exercises regularly. Conclusions support that movement exercises in the classroom are important to teachers and students. There is some evidence that academics improved following the use of Brain Gym activities. Further research studies using experimental designs are warranted. Recommendations are that researchers study the effects of movement over a longer period of time and use in-depth Brain Gym methods.
Keywords: curricula; teaching; elementary education; academic guidance counseling; curriculum development; school counseling